2020
DOI: 10.1080/13880209.2020.1835996
|View full text |Cite
|
Sign up to set email alerts
|

Anemarsaponin BII inhibits the activity of CYP3A4, 2D6, and 2E1 with human liver microsomes

Abstract: Context Anemarsaponin BII is one of the most active saponins isolated from Anemarrhena asphodeloides Bunge (Asparagaceae), a commonly used Chinese traditional paediatric medicine. Objective This study investigates the effects of anemarsaponin BII on the activity of CYP450s to provide more guidance for the clinical use of anemarsaponin BII. Materials and methods Using various diagnostic substrates, the effects of a fixed concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“… 2020 ), and anemarsaponin BII was also revealed to inhibit the activity of CYP3A4 in a dose-dependent manner with the IC 50 value of 10.23 μM in the present study, which is consistent with the previous study (Wang M et al. 2020 ). Hence, the inhibition of CYP3A4 was speculated to be one of the potential mechanisms underlying the interaction of nobiletin with anemarsaponin BII.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 2020 ), and anemarsaponin BII was also revealed to inhibit the activity of CYP3A4 in a dose-dependent manner with the IC 50 value of 10.23 μM in the present study, which is consistent with the previous study (Wang M et al. 2020 ). Hence, the inhibition of CYP3A4 was speculated to be one of the potential mechanisms underlying the interaction of nobiletin with anemarsaponin BII.…”
Section: Discussionsupporting
confidence: 93%
“… 2020 ; Wang M et al. 2020 ). The rats in the nobiletin group were orally administrated with 50 mg/kg nobiletin alone.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of P450s was evaluated by corresponding metabolites using HPLC with Agilent 1260 Series Rapid Resolution HPLC. The reaction system was prepared with the following compositions: HLMs with certain protein concentrations, specific substrates of different isoenzymes, PBS buffer solution, plantainoside D or specific inhibitors, and an NADPH generating system as previously reported [ 16 , 17 ]. Besides dextromethorphan and quinidine were dissolved in water, other substrated, inhibitors, and plantainoside D were dissolved in methanol with a final concentration of 1% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…Cepharanthine, a biscoclaurine alkaloid, has been shown to prevent DDI via CYP2E1 in vitro human liver microsomes [ 71 ]. Anemarsaponin BII (ABII) is an active saponin and competitive inhibitor of CYP2E1 activity with half-maximal inhibitory concentration (IC50) and dissociation constant (Ki) values of 19.72 μM and 9.82 μM, respectively, suggesting a DDI between ABII and drugs metabolized by CYP2E1 [ 72 ]. A study conducted on rats and hepatic cells revealed that anti-tuberculosis drugs, such as rifampicin and isoniazid, induce liver injury by regulating the nucleotide-binding domain (NOD)-like receptor protein 3 (NLRP3) inflammasome and enhancing CYP2E1 mRNA expression [ 73 ].…”
Section: The Role Of Hepatic Cyp2e1 In Causal Toxicity and Potential ...mentioning
confidence: 99%